Neonatal deaths: prospective exploration of the causes and process of end-of-life decisions. Issue 2 (7th August 2015) - Hellmann, Jonathan; Knighton, Robin; Lee, Shoo K; Shah, Prakesh S
Abstract : Objective: To determine the causes and process of death in neonates in Canada. Design: Prospective observational study. Setting: Nineteen tertiary level neonatal units in Canada. Participants: 942 neonatal deaths (215 full-term and 727 preterm). Exposure and outcome: Explored the causes and process of death using data on: (1) the rates of withdrawal of life-sustaining treatment (WLST); (2) the reasons for raising the issue of WLST; (3) the extent of consensus with parents; (4) the consensual decision-making process both with parents and the multidisciplinary team; (5) the elements of WLST; and (6) the age at death and time between WLST and actual death. Results: The main reasons for deaths in preterm infants were extreme immaturity, intraventricular haemorrhage and pulmonary causes; in full-term infants asphyxia, chromosomal anomalies and syndromic malformations. In 84% of deaths there was discussion regarding WLST. WLST was agreed to by parents with relative ease in the majority of cases. Physicians mainly offered WLST for the purpose of avoiding pain and suffering in imminent death or survival with a predicted poor quality of life. Consensus with multidisciplinary team members was relatively easily obtained. There was marked variation between centres in offering WLST for severe neurological injury in preterm (10%–86%) and severe hypoxic-ischaemic encephalopathy in full-term infants (5%–100%). Conclusions and relevance: In Canada, the majority of physicians offered WLST to avoid pain and suffering or survival with a poor quality of life. Variation between units in offering WLST for similar diagnoses requires further exploration.